PRECIPITATION CALCULATION METHOD BASED ON PARAMETERIZATION OF DISTRIBUTION FUNCTION EVOLUTION AND ITS PERFORMANCE IN GLOBAL SPECTRAL ATMOSPHERIC MODEL - Akimov I.V. (My University, 2004)
A new method of precipitation calculation, based on cloud microphysics parameterization is presented. The main idea of the method is to parameterize the evolution of distribution function during precipitation formation process. Gravitational and turbulent coalescence of cloud particles are assumed to be the main processes leading to the rain formation. The method considers the precipitation formation in liquid and mixed phase clouds. The phase state of a cloudy layer is calculated as a function of temperature. The effects of precipitation forcing in underlying cloudy layers, melting and evaporation are taken into account. The proposed method was introduced to a large-scale condensation scheme of the global spectral atmospheric model of the Hydrometcentre of Russia. Numerical experiments with the new version of model were conducted. The numerical results were verified using precipitation observations. The experiments show that the new method improves the skill of precipitation forecast for lead times 24–72 h in summer and 24–36 h in spring.
Keywords: Weather forecast; Precipitation; Clouds; Microphysics; Numerical modeling; Numerical modeling